2012
DOI: 10.2144/0000113876
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Culture of Primary Osteocytes from the Long Bones of Skeletally Mature and Aged Mice

Abstract: The purpose of this work was to establish a methodology to enable the isolation and study of osteocytes from skeletally mature young (4-month-old) and old (22-month-old) mice. The location of osteocytes deep within bone is ideal for their function as mechanosensors. However, this location makes the observation and study of osteocytes in vivo technically difficult. Osteocytes were isolated from murine long bones through a process of extended collagenase digestions combined with EDTA-based decalcification. A tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(107 citation statements)
references
References 46 publications
2
104
0
1
Order By: Relevance
“…Recent data from the Bonewald laboratory has demonstrated that seven to nine sequential digests are needed to release true osteocytes from mouse bones [27]. This is consistent with our data in Fig.…”
Section: Resultssupporting
confidence: 92%
“…Recent data from the Bonewald laboratory has demonstrated that seven to nine sequential digests are needed to release true osteocytes from mouse bones [27]. This is consistent with our data in Fig.…”
Section: Resultssupporting
confidence: 92%
“…Primary bone cells were isolated as previously described with some modifications (Stern et al, 2012). Briefly, long bones were dissected from 5- or 22-month-old C57BL/6 male mice for cell death assay and from 3-month-old DMP1-GFP female mice for live imaging.…”
Section: Methodsmentioning
confidence: 99%
“…Although recent studies have described methods for extraction of primary osteocytes from mouse long bones,45 the yields are generally low and would not have been sufficient for our experimental purposes. Therefore, we have used the MLO‐Y4 cell line which serve as a good osteocyte model as they respond to mechanical stimulation by releasing prostaglandin‐E 2 ,46 ATP,47 and nitric oxide,48 integral to osteocytes’ orchestration of adaptive bone remodeling.…”
Section: Discussionmentioning
confidence: 99%